Decarboxylative Sulfinylation Enables a Direct, Metal‐Free Access to Sulfoxides from Carboxylic Acids. (9th September 2022) - Nguyen, Viet D.; Haug, Graham C.; Greco, Samuel G.; Trevino, Ramon; Karki, Guna B.; Arman, Hadi D.; Larionov, Oleg V.
Abstract: The intermediate oxidation state of sulfoxides is central to the plethora of their applications in chemistry and medicine, yet it presents challenges for an efficient synthetic access, limiting the structural diversity of currently available sulfoxides. Here, we report a data‐guided development of direct decarboxylative sulfinylation that enables the previously inaccessible functional group interconversion of carboxylic acids to sulfoxides in a reaction with sulfinates. Given the broad availability of carboxylic acids and the growing synthetic potential of sulfinates, the direct decarboxylative sulfinylation is poised to improve the structural diversity of synthetically accessible sulfoxides. The reaction is facilitated by a kinetically favored sulfoxide formation from the intermediate sulfinyl sulfones, despite the strong thermodynamic preference for the sulfone formation, unveiling the previously unknown and chemoselective radicalophilic sulfinyl sulfone reactivity. Abstract : The new metal‐free cross‐coupling of carboxylic acids and sulfinates provides a direct and modular access to sulfoxides by a photocatalytic process that has unveiled the unexplored chemoselective radicalophilic reactivity of intermediate sulfinyl sulfones and enabled the conjunctive coupling of two carboxylic acids, revealing broad new chemical space accessible by the merger of the two coupling partner classes of emergent synthetic importance.